Facemask Alternatives in Veterinary Medicine in the Context of COVID-19 Shortages - Purens, Abigail Gavra Michaelson (Frontiers in Veterinary Science, 2020)
The COVID-19 pandemic has caused a widespread shortage of facemasks and other personal protective equipment in veterinary medicine without clear, research-based guidance on alternatives to FDA-certified disposable surgical masks. In the absence of detailed veterinary research, an in-depth review of the human medical literature was conducted to evaluate the viability of reusable, sterilizable cloth, medical textile, or other material alternatives that may be quickly manufactured and used by veterinarians. The results at the time of publication support the AVMA, CDC, and WHO recommendations to extend use, reuse, and resterilize facemasks before considering using a homemade facemask. Pending further research, or until and unless the FDA certifies a reusable homemade mask or design, the substitution of homemade masks for FDA-certified surgical masks should only be considered as a last resort. Most homemade masks are not suitable replacements for N95 FFRs. If a homemade facemask must be made, the following materials and testing guidelines are suggested: - densely woven cotton fabric (> 270 thread count), medical textile, or other impermeable, breathable material that can be laundered and resterilized - make pleated or fitted pocket style facemasks to maximize fit - make masks with two sets of ties, not elastics, to endure laundering and autoclaving - internal wire or fabric tape may be used to mold masks over the nose - filter material should be designed for use near mucus membranes, such as facial tissue or paper towel - if possible, fit test homemade masks against an FDA-certified surgical mask as a control - if higher filtration efficiency is required, test according to the FDA Enforcement Policy for Face Masks and Respirators During the Coronavirus Disease (COVID-19) Public Health Emergency - Maintain enough masks to change as frequently as one would change disposable surgical masks to maintain appropriate hygiene